Conceptual design of an alignment device for transfemoral prosthesis (2021)
ABSTRACT : The alignment of lower limb prosthesis is one of the most significant procedures for prosthetic adaptation since it allows greater comfort and fulfillment of the prosthesis function. Prosthetic misalignment can lead to severe consequences for the patient, such as gait instability and increased load on the residual limb. The fitting and alignment of the prosthetic system is a highly subjective procedure that relies mainly on the professional experience of the prosthetist. This study aims to design a prototype of a low-cost alignment device for lower transfemoral prosthesis to be used temporarily during the prosthesis static alignment. The conceptual design methodology was implemented. The device was modeled in SolidWorks, and the mechanical resistance of the device was determined in a finite element analysis in Ansys. Among the tested materials, CarbonFil exhibited the best behavior showing promising results for a 3D printed alignment device prototype. The viability of this device’s massive production should be considered to further reduce its cost and be implemented in a larger number of prosthetic centers worldwide.